Summer of the monkeys - Rawls, Wilson (New York : Doubleday, 1976)
In the late 1800's, a fourteen-year-old Ozark mountain boy spends the summer trying to recapture monkeys escaped from a traveling circus.
Booklist.
Elem. School Library Collection.
Wilson's Junior High School.
5.1
5.9
7-10.
Keywords: Monkeys -- Fiction; Oklahoma -- Fiction